1996
DOI: 10.1242/dev.122.6.1909
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct determination in Drosophila: roles of the EGF receptor signaling pathway and the transcription factors Fork head and Trachealess

Abstract: Organogenesis in Drosophila embryos begins at 4–5 hours of development as the expression of organ-specific genes is initiated. The salivary primordium, which occupies the ventral epidermis of parasegment 2, is among the earliest to be defined. It is soon divided into two distinct regions: the more dorsal pregland cells and the more ventral preduct cells. We show that it is the opposing activities of the Drosophila EGF receptor (DER) signaling pathway and the Fork head transcription factor that distinguish thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Of the significantly differentially expressed proteins, the ones with changes lower than 2-folds were discarded in the following analysis. is a transcription factor playing an important role in salivary duct determination in Drosophila, 41 and it has been proposed to be essential for the formation of the trachea and the ASG in the silkworm. 5 However, compared with the other two particular stages, there were far fewer genes specifically expressed during the feeding stages.…”
Section: ' Discussionmentioning
confidence: 99%
“…Of the significantly differentially expressed proteins, the ones with changes lower than 2-folds were discarded in the following analysis. is a transcription factor playing an important role in salivary duct determination in Drosophila, 41 and it has been proposed to be essential for the formation of the trachea and the ASG in the silkworm. 5 However, compared with the other two particular stages, there were far fewer genes specifically expressed during the feeding stages.…”
Section: ' Discussionmentioning
confidence: 99%
“…Several genes that are involved in determining tubulogenesis during embryonic development are identical for both the tracheal system and for SGs (Kuo et al, 1996;Henderson & Andrew, 2000;Jin et al, 2001;Kerman et al, 2006). Based on our observations, one can anticipate that at least some of the genes which affect taenidial formation in a tracheal system (Öztürk-Çolak et al, 2016) may be different from the genes required to determine and maintain taenidia in SG ducts.…”
Section: Discussionmentioning
confidence: 64%
“…In the course of our SEM studies on the surface properties and internal substructure of exocytosed and expectorated glue (Beňová-Liszeková et al, 2019b), we found that the internal lining of the tubular, non-secretory structure of the SG, i.e., the duct that develops during embryogenesis by the coordinated action of a differently expressed set of genes, in contrast to the SG proper (Kuo et al, 1996;Jones et al, 1998;Yao & Sun, 2005), shows peculiar structures resembling tracheal taenidia. Using classical light microscopy, the potential presence of taenidial-like chitinous circumferential rings in Drosophila SG duct was noticed by Robertson (1936) andRoss (1939).…”
Section: Light and Phase Contrast Microscopymentioning
confidence: 90%
“…Analysis of the most upregulated genes within the salivary gland placodal in comparison to the epidermal dataset revealed 86 genes (Fig.1D). Of these, only 14 had previously been found to show salivary gland defects when mutants were analysed [ pipe (Zhu et al , 2005), pasilla (Seshaiah et al , 2001), CrebA (Andrew et al , 1997), Btk29/Tec29 (Chandrasekaran & Beckendorf, 2005), PH4alphaSG2 (Abrams et al , 2006), sage (Chandrasekaran & Beckendorf, 2003; Fox et al , 2013), myospheroid (Bradley et al , 2003), fkh (Jürgens et al , 1984), eyegone (Isaac & Andrew, 1996; Kuo et al ., 1996), fog (Lammel & Saumweber, 2000; Nikolaidou & Barrett, 2004), Scr (Mahaffey & Kaufman, 1987; Panzer et al , 1992), KDEL-R (Abrams et al , 2013), crossveinless-c (Kolesnikov & Beckendorf, 2007), ribbon (Bradley & Andrew, 2001)], 30 had been described to be expressed within the salivary gland by microarray analysis [ nemuri , CG13159 , Hsc70-3 , windbeutel , Papss , CG14756 , PH4alphaSG1 , SsRbeta , sallimus , TRAM , Sec61beta , twr , piopio , Spase12 , PDI , CG7872 , Surf4 , Calr , CHOp24 , par-1 , p24-1 , Trp1 , Sec61gamma , nuf , RpS3A , Spase25 , ERp60 , Prosap , Fas3 , fili , (Fox et al ., 2010; Loganathan et al ., 2016; Maruyama et al ., 2011)] and 22 could be identified to be expressed in the salivary glands or placode through publicly available in situ hybridisation databases [ Tpst , CG5493 , sano , CG5885 , Sec61alpha , Tapdelta , Gmap , l(1)G0320 , nyo , NUCB1 , Manf , bai , ergic53 , CG32276 , eca , GILT1 , Spase22-23 , Glut4EF , CG17271 , bowl , CG9005 , Tl; (Hammonds et al , 2013; Lecuyer et al , 2007; Tomancak et al , 2002; Tomancak et al , 2007; Wilk et al , 2016). 17 genes we highly upregulated that had not been previously linked to salivary gland morphogenesis or function by any of the above means ( SoxN , ogre , CG34190 , CG46385 , CG6356 , Mob2 , link , Spp , MYPT-75D , Pde9 , Fkbp14 , Gp93 , w , ImpL2 , CG9095 , Atf6 , dpy ).…”
Section: Resultsmentioning
confidence: 99%
“…Fkh in the rest of the placodal cells instructs the morphogenesis and activates a secretory programme (Haberman et al , 2003; Jones et al , 1998). EGFR mutants do not form a duct and internalise salivary gland tubes with two closed ends (Kuo et al , 1996; Maybeck & Röper, 2009).…”
Section: Introductionmentioning
confidence: 99%